Amazing Grace Adams - Littlewood, Fran (Henry Holt and Company, 2023)
"A funny, touching, unforgettable story of an invisible everywoman pushed to the brink-who finally pushes back. Grace Adams gave birth, blinked, and now suddenly she is forty-five, perimenopausal and stalled-the unhappiest age you can be, according to the Guardian. And today she's really losing it. Stuck in traffic, she finally has had enough. To the astonishment of everyone, Grace gets out of her car and simply walks away. Grace sets off across London, armed with a £200 cake, to win back her estranged teenage daughter on her sixteenth birthday. Because today is the day she'll remind her daughter that no matter how far we fall, we can always get back up again. Because Grace Adams used to be amazing. Her husband thought so. Her daughter thought so. Even Grace thought so. But everyone seems to have forgotten. Grace is about to remind them...and, most important, remind herself" --